The limits of historiography: genre and narrative in ancient historical texts - Kraus, Christina Shuttleworth; Kraus, Christina S. (Mnemosyne <Leiden> / Supplementum, 1999)
Social pleasures in early Chinese historiography and philosophy / David Schaberg -- Knowledge and skepticism in ancient Chinese historiography / Wai-Yee Li -- Local versus general history in Old Hittite historiography / Alexander Uchitel -- Commemoration, writing, and genre in ancient Mesopotamia / Piotr Michalowski -- The Persian kings and history / Heleen Sancisi-Weerdenburg -- History, historiography, and the use of the past in the Hebrew Bible / Thomas M. Bolin -- Thucydides' Persian wars / Timothy Rood -- Guiding metaphor and narrative point of view in Livy's Ab urbe condita / Mary Jaeger -- Tacitus' Histories and the theory of deliberative oratory / David S. Levene -- Jugurthine disorder / Christina S. Kraus -- Universal perspectives in historiography / Katherine Clarke -- Genre, convention, and innovation in Greco-Roman historiography / John Marincola -- Epilogue / Christopher Pelling